Variations in the use and availability of formal and informal care at the end of life over time and space - Schneider, Anna; Atherton, Iain (International Journal of Population Data Science, 2019)
Background In light of increasing death rates and a high need for palliative care at the end of life, it is important to plan formal care resources and understand in what ways informal care may alleviate the pressure on healthcare services. A piece to this information puzzle is understanding spatial variations in the use and availability of formal and informal care and how these develop over time. Aim This paper explores spatial variations in place of death and living arrangements (as proxy for informal care availability) in the last year of life in Scotland, comparing two time points. Data Analysis is based on population data from the Scottish Census 2001 and 2011 that was linked with NHS data and death records data for everyone who passed away within a year of census enumeration. Geographic data includes the Scottish urban-rural classification and healthboards. Methods Data was linked via probability linkage. Descriptive analysis and regression models will be presented. Results and Conclusions The study population comprises 49,356 cases from 2001/02 and 46,473 from 2011/12. Understanding how care use has changed over time and varies spatially is key to health and social care resource planning and social policy making.